STUDENT SCIENTIFIC ATTITUDES TO THE VESTA SOFTWARE AS LEARNING MEDIA OF CRYSTAL STRUCTURE - Nadiyyah, Khoirotun; Aprianti, Rika; Nisa, Uliya Khoirun; Gusti, Valeria Yekti Kwasaning (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2023)
In solid-state physics, the crystal structure was the subject that one must learn and understand. In providing an understanding of the concept, educators need to use learning media. At this time, learning media has developed rapidly, especially digital visual media. Vesta Software is a media that can visualize and simulate crystal structures in 3D. This research aimed to analyze students' scientific attitudes to the Vesta software as a learning media of crystal structure. Data collection used a Likert scale with a scientific attitude questionnaire on curiosity, honesty, perseverance, critical thinking, open-mind, cooperation, and creativity. The method in this research was descriptive qualitative using data triangulation. That was obtained, the seven students' scientific attitudes were "very good", and the most dominant was "curiosity" with 88.03%. Furthermore, Vesta software could be an alternative learning media to crystal structures because it was easy to use and learn, increasing the student’s knowledge and understanding.